Co3O4/rGO Catalysts for Oxygen Electrocatalysis: On the Role of the Oxide/Carbon Interaction. Issue 4 (7th February 2019) - Abidat, I.; Cazayus, E.; Loupias, L.; Morais, C.; Comminges, C.; Napporn, T. W.; Portehault, D.; Durupthy, O.; Mamede, A-S.; Chanéac, C.; Lamonier, J.-F.; Habrioux, A.; et al.
Abstract : The reduction degree of graphene oxide substrate governs the activity and stability of Co3 O4 /rGO nanocomposites toward oxygen reduction reaction and oxygen evolution reaction. In this work, Co3 O4 nanoparticles with narrow size distribution were uniformly deposited onto graphene oxide materials with different reduction degrees, by using a microwave-assisted hydrothermal method. The physicochemical characterization of these nanocomposites indicates that oxygenated groups grafted onto a reduced graphene oxide surface allow creating strong interactions between the carbon-based substrate and Co3 O4 nanocrystals. The obtained results denote that the electrocatalytic activity and stability of these nanocomposites toward the ORR and OER depend on the entanglement between the strength of the carbon/oxide interaction and the electronic conductivity of the substrate.